Expression of dominant-negative src-homology domain 2-containing protein tyrosine phosphatase-1 results in increased Syk tyrosine kinase activity and B cell activation. - Dustin, L; Plas, DR; Wong, J; Hu, Y; Soto, C; Chan, A; Thomas, M (1999)
The Src-homology domain 2 (SH2)-containing cytoplasmic tyrosine phosphatase, SHP-1 (SH2-containing protein tyrosine phosphatase-1), interacts with several B cell surface and intracellular signal transduction molecules through its SH2 domains. Mice with the motheaten and viable motheaten mutations are deficient in SHP-1 and lack most mature B cells. To define the role of SHP-1 in mature B cells, we expressed phosphatase-inactive SHP-1 (C453S) in a mature B cell lymphoma line. SHP-1 (C453S) retains the ability to bind to both substrates and appropriate tyrosine-phosphorylated proteins and therefore can compete with the endogenous wild-type enzyme. We found that B cells expressing SHP-1 (C453S) demonstrated enhanced and prolonged tyrosine phosphorylation of proteins with molecular masses of 110, 70, and 55-60 kDa after stimulation with anti-mouse IgG. The tyrosine kinase Syk was hyperphosphorylated and hyperactive in B cells expressing SHP-1 (C453S). SHP-1 and Syk were coimmunoprecipitated from wild-type K46 cells, K46 SHP-1 (C453S) cells, and splenic B cells, and SHP-1 dephosphorylated Syk. Cells expressing SHP-1 (C453S) showed increased Ca2+ mobilization, extracellular signal-regulated kinase activation, and homotypic adhesion after B cell Ag receptor engagement. Thus, SHP-1 regulates multiple early and late events in B lymphocyte activation.